Plasma microRNA‐192‐5p can predict the response to neoadjuvant chemotherapy and prognosis in esophageal cancer. Issue 4 (26th December 2022) - Furuke, Hirotaka; Konishi, Hirotaka; Arita, Tomohiro; Kataoka, Satoshi; Shibamoto, Jun; Takabatake, Kazuya; Takaki, Wataru; Shimizu, Hiroki; Yamamoto, Yusuke; Komatsu, Shuhei; Shiozaki, Atsushi; Fujiwara, Hitoshi; et al.
Abstract: Esophageal cancer (EC) is the sixth leading cause of cancer‐related death worldwide. Recently, neoadjuvant chemotherapy (NAC) before curative surgery has become a standard treatment for clinical stage II or III EC patients. Some EC patients receive a complete response (CR) by NAC; thus, curative surgery may be unnecessary for such patients. MicroRNA levels in plasma have the potential to be a predictor of response to NAC. In the present study, we focused on miR‐192‐5p, which is highly expressed in EC tissue. The purpose was to investigate the correlations between levels of plasma miR‐192‐5p and the response to NAC. Furthermore, molecular functions of miR‐192‐5p associated with chemosensitivity were examined using EC cell lines. The levels of miR‐192‐5p in plasma before surgery were evaluated in 113 EC patients. Sixty‐nine patients received NAC. miR‐192‐5p levels in the CR group were significantly higher than in the other groups ( p = 0.002). The downregulation of miR‐192‐5p in the EC cell line inhibited sensitivity to cisplatin, and the overexpression of miR‐192‐5p in the EC cell line promoted sensitivity to cisplatin. miR‐192‐5p regulated sensitivity to cisplatin by targeting ERCC3 and ERCC4. Plasma miR‐192‐5p could be used as a predictor of response to chemotherapy and prognosis in EC patients. Abstract : Expression of miR‐192 in esophageal cancer regulated sensitivity to cisplatin by targeting ERCC3 and ERCC4. Plasma miR‐192 may be used as a predictor of response to chemotherapy in esophageal cancer patients.